Pengaruh Teknologi Informasi terhadap Hukum dalam Masyarakat - Tamaulina Br. Sembiring; Andeas Rezeki Lombu; Armen Fernando; Muhammad Arfansyah; Putri Theresia Pasaribu; Ryan Samosir (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Information technology has brought profound transformation in various aspects of life, including in the context of law in Indonesian society. In facing the complexities and dynamics of technological development, a deep understanding of the associated challenges and implications has become an urgent need. This research aims to investigate the impact of information technology on law within Indonesian society and to identify appropriate policy recommendations to address the emerging challenges. A qualitative approach is used in this study, gathering data from various relevant sources and systematically processing it. The results of the study indicate that the development of information technology (IT) has had a significant impact on the legal system in Indonesia, particularly in improving efficiency, transparency, and accessibility of law for society.